Brief Counseling 5A Pharmacist with Illustrated Booklet Improves Outcomes in Anemic Pregnant Women: A Quasi-Experimental Study - Rizka Novia Atmadani; Akrom Akrom; Siti Urbayatun; Dian Novanda Ramadhani; Nur Laily Rizky Amalia (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Anemia during pregnancy remains a significant global health concern, affecting 25–50% of pregnant women worldwide. Although iron and folic acid supplementation programs (TTD) are widely implemented, adherence among pregnant women is frequently compromised due to various barriers Method: A quasi-experimental study with a pre-post control group design was conducted across public health centers in Malang City. The intervention group received brief pharmacist counseling accompanied by illustrated booklets, while the control group received routine standard care. Result: Post-intervention analyses indicated significant improvements in knowledge scores, increased adherence to TTD, and positive behavioral changes in the intervention group. Statistical assessment using the Wilcoxon Signed Rank test revealed significant differences between pre and post-test measurements for knowledge, adherence, and behavior (p < 0.05). Conclusion: Brief pharmacist counseling supplemented with illustrated booklets resulted in substantial enhancements across all measured outcomes compared to standard care, underscoring the effectiveness of this intervention for managing anemia during pregnancy.